ANALYSIS OF CODE-MIXING FOUND IN THE CORBUZIER PODCAST ON YOUTUBE - Lutfio Indra Permana; Malikatul Laila (Universitas Muhammadiyah Surakarta, 2023)
Podcast is a platform for people to talk about something off-air which can be found on YouTube. This study aims to identify the type of code-mixing and to explain the reasons of using code-mixing in the Podcast. This qualitative research collected the data from the speakers’ utterances in the YouTube video entitled “AZKA CORBUZIER LOH UDAH PACARAN SKRG!” using non-participant observation and documentation. The result revealed that there are 172 data containing code-mixing. Firstly, in Muysken’s typology of code-mixing theory, there are: 99 data of alternation type, 72 data of insertion, and one data of congruent lexicalisation. Secondly, the reasons of code-mixing involved two theories: Hoffman’s theory and Bhatia and Ritchie’s theory. In Hoffman’s theory, there are 124 data as talking about a particular topic, 19 data as emphasising the intention, 11 data as clarifying by using repetition, six data as uncategorised, five data as being emphatic about something, three data as quoting somebody else, and two data as expressing interjection and as expressing group identity. In Bathia and Ritchie’s theory: (1) participants: father and son relation; (2) situational factors: podcast setting, involving private domain, intimate and informal conversation, and social variables: 14 years old and 44 years old and wealthy family; (3) message-intrinsic consideration: quotation, reiteration, message-qualification, topic-comment/relative clause, hedging, and interjection/sentence filler; (4) language attitude, dominance, and security: both speakers have positive attitude toward each other’s code-mixing, balanced language dominant, and respectable while exchanging code-mixing.Keywords: code-mixing, sociolinguistics, non-participant obsevation, podcast, bilingualism